2007
DOI: 10.1159/000099944
|View full text |Cite
|
Sign up to set email alerts
|

Can Donor Implantation Renal Biopsy Predict Long-Term Renal Allograft Outcome?

Abstract: Background: Donor kidney implantation biopsy (IB) is performed on a regular basis, particularly as part of clinical studies. Objective: To determine the utility of donor implantation renal biopsy to predict the long-term renal allograft outcome. Methods: A Medline search for studies in English was performed with the following key words: implantation biopsy, renal transplantation and long-term outcome. Results: Sixteen trials involving 8,122 kidney transplants were identified, of which 6 were prospective studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…Patients who would benefit from a kidney transplant may have to remain on the waitlist because kidneys with mild interstitial fibrosis are being rejected for transplantation [19]. Our study conducted in native kidneys is consistent with several studies in the transplant literature showing that a mild to moderate degree of fibrosis on time-zero biopsy does not necessarily predict worse graft function in living or deceased donor kidney transplantation [20-23]. …”
Section: Discussionsupporting
confidence: 82%
“…Patients who would benefit from a kidney transplant may have to remain on the waitlist because kidneys with mild interstitial fibrosis are being rejected for transplantation [19]. Our study conducted in native kidneys is consistent with several studies in the transplant literature showing that a mild to moderate degree of fibrosis on time-zero biopsy does not necessarily predict worse graft function in living or deceased donor kidney transplantation [20-23]. …”
Section: Discussionsupporting
confidence: 82%
“…It is obvious that higher age of a kidney is independently associated with chronic histologic damage, as was described in autopsy studies (314). From this, it is no surprise that higher kidney age is an independent predictor of tubular atrophy, interstitial fibrosis, and functional impairment after renal transplantation, which was shown in protocol biopsy studies in adult and pediatric renal allograft recipients (85,261,315,316). However, these studies not only showed an association with nonspecific chronic histologic damage, but also demonstrated an association of higher donor age with medial arteriolar hyalinosis suggestive of CNI nephrotoxicity (85,261).…”
Section: Local Renal Susceptibility Factors For Cni Nephrotoxicitymentioning
confidence: 85%
“…2831 Cosio et al have demonstrated graft interstitial fibrosis (7%), tubular atrophy (25%), and arterial hyalinosis (10%) in biopsies taken from living donor kidneys. 32 They reported that interstitial fibrosis correlated well with both function and eventual graft survival.…”
Section: Discussionmentioning
confidence: 99%